Phyto-Mediated Route for Nickel Oxide Nanoparticle Synthesis Using Microtrichia perotitii DC Extract: Characterization and Antibacterial Activity - Danjuma, Friday; Oluwaseyi, Bamigboye; Iyanuoluwa, Owoyemi; Atinuke, Oyabambi; Olaifa, Joshua; Obaleye, Miracle (University of Thi-Qar Journal of Science, 2025)
The growing demand for sustainable nanomaterials has intensified interest in green synthesis routes utilizing plant-derived biomolecules as reducing and stabilizing agents. This study reports, for the first time, the biosynthesis of nickel oxide nanoparticles (NiO NPs) using Microtrichia perotitii DC leaf extract, a medicinal plant rich in bioactive phytochemicals including flavonoids, alkaloids, tannins, phenolics, and saponins. Nickel (II) chloride hexahydrate served as the metal precursor, while the phytochemicals facilitated both nanoparticle formation and stabilization. The synthesized NiO NPs were comprehensively characterized using UV-visible spectroscopy, Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM) with energy-dispersive X-ray spectroscopy (EDX), and thermogravimetry/differential thermal analysis (TG/DTA). XRD analysis confirmed the formation of crystalline nanoparticles with an average crystallite size of 24 nm and a cubic bunsenite phase. FTIR spectroscopy revealed a characteristic Ni-O stretching vibration at 651 cm⁻¹, confirming successful NiO formation. SEM imaging showed irregular, agglomerated nanostructures, while TG/DTA analysis demonstrated good thermal stability with major decomposition occurring at 473°C, attributed to the removal of phytochemical residues. Antibacterial assays demonstrated strong inhibitory effects of the biosynthesized NiO NPs, particularly against Gram-positive bacteria, including Bacillus subtilis (18.8 ± 0.6 mm) and Staphylococcus aureus (19.6 ± 0.4 mm) at 100 µg/mL concentration. Although the activity was slightly lower than ciprofloxacin (5 µg/disc: 22.4 ± 0.5 mm and 23.1 ± 0.43 mm, respectively), it indicates significant antibacterial potential. Gram-negative strains exhibited comparatively lower sensitivity, likely due to their protective outer membrane barrier.